Enabling rural innovation in Africa : An approach for integrating farmer participatory research and market orientation for building the assets of rural poor - Sanginga, Pascal C.; Best, R.; Chitsike, C.; Delve, Robert J.; Kaaria, Susan K.; Kirkby, Roger A. (2004)
Agricultural research and development organizations are increasingly under pressure to shift from enhancing productivity of food crops to improving profitability and competitiveness of small-scale farming, and linking smallholder farmers to more profitable markets. What is not obvious however, is how to make small-scale farming more market orientated, and how to effectively integrate participatory research approaches to marketing and agroenterprise development. This paper outlines an integrated approach for demand-driven and market-orientated agricultural research and rural agro-enterprise development. This approach termed Enabling Rural Innovation (ERI) offers a practical framework to link farmer participatory research and market research in a way that empowers farmers to better manage their resources and offers them prospects of an upward spiral out of poverty. ERI uses participatory processes to build the capacities of farmers’ groups and rural communities in marginal areas to identify and evaluate market opportunities, develop profitable agroenterprises, intensify production through experimentation, while sustaining the resources upon which their livelihoods depend. The approach emphasizes integrating scientific expertise with farmer knowledge, strengthening social organization and entrepreneurial organizations through effective partnership between research, development and rural communities. By strengthening human and social capital, ERI encompasses effective and proactive strategies for promoting gender and equity in the access to market opportunities and improved technologies, and in the distribution of benefits and additional incomes.. Results of action research applying the ERI approach in pilot sites in Malawi, Uganda and Tanzania show that small-scale farmers are not always attracted by higher economic returns. Rather they use a range of economic and non-economic criteria for selecting their existing crops and livestock for new markets, as well as new crops for new markets. Evaluation of market opportunities stimulates farmers’ experimentation to reduce risks, access new technologies, and improve the productivity and competitiveness of the selected enterprises. Lessons learned suggest that building and sustaining quality partnerships between research and development organizations, government, private agribusiness sector; and building necessary amount of human and social capital over a certain period of time are critical for achieving success in small- scale agroenterprise development. This however, requires that an explicit scaling up strategy be mapped out to link successful community processes to meso and macro level market institutions at the national and regional levels.